Digital Multiliteracy Flipbooks: A Novel Pedagogical Approach to Observational Report Writing in High Schools - Azmi Faqihatul Ilmi; Sujinah Sujinah; Achmad Hidayatullah (Journal of Educational Management Research, 2026)
Writing skills are an essential competency in Indonesian language learning; however, teaching observational report writing continues to face challenges, including low student engagement, limited understanding of the material, and difficulties in generating ideas. This study aimed to develop a multiliteracy-based flipbook and evaluate its feasibility, effectiveness, and students’ responses as a digital teaching material for observational report writing. The study employed a Research and Development approach using the Four-D model, consisting of the define, design, develop, and disseminate stages. Data were collected through expert validation, pretests, posttests, classroom observations, and student response questionnaires. The findings revealed that the flipbook achieved an average expert validation score of 89.59%, indicating that it was highly feasible for classroom implementation. Students’ average writing scores improved from 71 on the pretest to 84 on the posttest. In addition, teacher and student learning activities each reached 97%, categorized as very good, while student responses reached 81%, indicating positive acceptance. These findings suggest that the multiliteracy-based flipbook is a feasible and effective digital teaching material that enhances students’ writing skills, promotes active learning, and supports the integration of multiliteracy pedagogy in Indonesian language instruction.